2013
DOI: 10.1177/0002764213515227
|View full text |Cite
|
Sign up to set email alerts
|

The Let Down Effect

Abstract: Using experimental design, this study compares first-time voters' gratifications and uses of a traditional News 1 format with the increasingly popular fake news format. The data here found that while indeed young people may have initially assessed a greater level of gratification associated with the fake news genre, the group was significantly "let down" after exposure to such a program. Though first-time voters understand that traditional surveillance-type information-seeking activities are better associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The format in which fake news is embodied can also be a moderator of its effects. Studies have shown that viewers of satirical or parodied content have a more comprehensive knowledge of the news agenda than those who watch televised news only, as the blend of seriousness and humour is a reliable source of information, satisfying two types of gratifications: the need of entertainment and the need of information (Browning & Sweetser, 2014). The problem is that fake news can infiltrate much easier within a transmitted opinion about a piece of information that within the information itself.…”
Section: Effects and Moderators Of Fake News Effectsmentioning
confidence: 99%
“…The format in which fake news is embodied can also be a moderator of its effects. Studies have shown that viewers of satirical or parodied content have a more comprehensive knowledge of the news agenda than those who watch televised news only, as the blend of seriousness and humour is a reliable source of information, satisfying two types of gratifications: the need of entertainment and the need of information (Browning & Sweetser, 2014). The problem is that fake news can infiltrate much easier within a transmitted opinion about a piece of information that within the information itself.…”
Section: Effects and Moderators Of Fake News Effectsmentioning
confidence: 99%